A Missouri railroad pioneer the life of Louis Houck - Rhodes, Joel P., 1967- (University of Missouri Press, 2008)
"Examines the life of a self-taught Cape Girardeau railroader whose network of more than five hundred miles of track transformed southeastern Missouri in the late nineteenth century. Louis Houck also helped establish the college now known as Southeast Missouri State University and wrote a noted history of Missouri"--Provided by publisher.